Contemporary issues on compensation in the perspective of the land acquisition act 1960 - Harun, Azmi (IIUM Press, International Islamic University Malaysia, 2017)
The primary purpose of this book is to examine the issues related to compensation. The law and practice concerning the assessment of compensation is set out and the problem encountered in their application is discussed in some detail. Chapter Two focuses on the main theme which arises in the area of compensation. The first part of the analysis will examine the bases of compensation. A later section of this chapter is devoted to examine the constraints relating to the assessment of compensation. The present law will be considered, to be followed by a discussion of other principles, which are becoming of relevance in this area. The possible test for determining development value will be evaluated as part of this analysis. Chapter Three is devoted to examining the old concept of “value to the owner” as an alternative to the market value criteria as the measure of compensation. The discussion is an attempt to unravel the uncertainty that is said to be the trademark of the concept.